Post occupancy evaluation sustainability assessment framework for commercial office buildings - Shika, Suleiman Aliyu (2014)
Researchers have studied the concept of building performance and their evaluation over the years. The growth and use of performance assessment methods for existing buildings have contributed to sustainability in various stages of building performance especially in determining the occupant's needs and expectations of sustainability in office buildings. Assessment tools have been developed with different evaluation criteria based on the condition to suit the characteristics of the countries for which the tools were designed, hence applying sustainability assessment tool in rating existing building can be effective in optimized decision making to use them. This study explores the process of developing assessment criteria to assess sustainability in buildings. One of the primary and main steps in each criterion is arranging the assessment items, and then the assessment criteria are made based on relevant performance criteria and parameters.